FAKTOR DETERMINAN KINERJA PEGAWAI DI BRI CABANG SEMARANG A.YANI - Sopi Sopi; Zumrotun Nafiah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
Performance determinants include; education, motivation and compensation. These factors are quite important that can improve performance. This study aims to explain whether there is an influence of education, motivation and compensation on employee performance. So that through the results of this study are expected to be a reference for leaders in managing the organization. In this study there are three independent variables namely education, motivation and compensation and one dependent variable is employee performance. At this time in the era of the industrial revolution 4.0, which was marked by; big data / giant data, internet of think, labor knowledge, and long life education. Since the beginning of the life of mankind until an infinite period, very much determined by the ability of mastery of science and technology. Science and technology can not be separated with the advancement of education levels. Education is the base of all changes both individually, groups and the State. Employee performance is largely determined by the education they have, the higher the education the higher the performance and vice versa. The population in this study were employees of BRI AHMAD YANI SEMARANG BRANCH of 60 people and all of them were sampled. The results of the analysis with SPSS 23 statistical tools obtained multiple linear regression equation Y = 0.505 X1 + 0.175 X2 + 0.408 X3. The results of multiple linear regression equations show that there is a positive and significant effect between education on employee performance at BRI AHMAD YANI SEMARANG BRANCH (t-test 6.314> t table 0.05), motivation on employee performance at BRI AHMAD YANI SEMARANG BRANCH (t-test 2.160> t table 0.05), and compensation for employee performance at BRI AHMAD YANI SEMARANG BRANCH (t-test 5.108> t table 0.05). While jointly (simultaneously) the effect of education, motivation and compensation influence and significant effect on employee performance at BRI AHMAD YANI SEMARANG BRANCH (f test = 44.692> f table = 0.05). The influence of both research variables is very strong with a correlation value of 69.0% for employee performance in BRI AHMAD YANI SEMARANG BRANCH is influenced by motivation education and compensation. The remaining 31.0% employee performance in BRI AHMAD YANI SEMARANG BRANCH is influenced by other variables that affect Employee performance.